Power Management with Dynamic Power Adaption for a Rotational Energy Harvester in a Maritime Gearbox. (November 2019) - Esch, J; Schillinger, D; Stojakov, D; Hoffmann, D; Manoli, Y
Abstract: Rotational Energy Harvesting becomes increasingly important for rotating sensor applications. Most of these applications rotate with changing revolution speed, which is a significant challenge for the energy harvesting system. This work presents an energy harvesting system for rotational motion with a new power management concept to generate energy for a wireless condition monitoring system. The challenge is to generate enough energy with a high efficiency factor at the minimum revolution speed but also to avoid problems with energy excess and high voltages at the maximum revolution speed. The power management includes solid state relays for coil switching to avoid the generation of excess energy that would lead to increased temperature. At 500 rpm the energy harvester generates 193 mW. With an efficiency of 54% the power management provides an output power of 106 mW.